STUDI EKSPERIMEN PENGARUH PENAMBAHAN GAS HHO TERHADAP DISTRIBUSI TEMPERATUR API PADA KOMPOR TEKAN (BLOW-TORCH BURNER) BERBAHAN BAKAR KEROSENE+OLI BEKAS - Sari, Handini Novita (Universitas Hasyim Asy'ari, 2016)
The quality of combustion in stoves press (blow-torch burner) can be improved in various ways. One way is use renewable fuel that is HHO gas, which is produced from HHO generator dry type, also by utilizing the waste oils as fuel. The addition of HHO gas and used oil in stove press (blow-torch burner) burning will reduce the volume of kerosene consumption.This study was conducted using true experiment with fuel kerosene + used oil as a control group were then compared to the fuel mix used oil and kerosene + HHO gas. Tests conducted on a test stove and combined with a self-designed HHO generator. HHO gas production rate that entering to combustion chamber as much as 2.3 LPM. HHO Gas and vapor mixing kerosene + used oil are combined in premix using ejector, by varying the fuel valve opening at openings 25% and 50%. Parameters measured were flame fire structure based on the contours of isothermal, the temperature distribution at each altitude, high fire, flame width, power fuel and conduction heat transfer that occurs.Based on the results of research showed that the fuel valve openings and the addition of HHO gas on the stove press (blow-torch burner) burning led to a decline in flame height, increase the width of the flame, increasing the temperature distribution, power fuel, as well as conduction heat transfer with increasing fuel valve openings and the addition of HHO gas.Keywords: stove press (Blow-torch burner), kerosene, used oil, HHO gas, HHO generator.Studi Eksperimen Pengaruh Penambahan Gas HHO37